The Influence Of Fundamental Variables On Prices Shares In Pt. Indo Tambangraya Mega Tbk Which Is Registered At Indonesian Stock Exchange - Amin, Andi Mustika; Nurman; Aslam, Annisa Paramaswary; Musa, Muh Ichwan; Ramadhani, Gina (PT Maju Malaqbi Makkarana, 2024)
This research aims to determine the influence of fundamental variables on Share Prices at PT Indo Tambangraya Mega Tbk. This research uses quantitative and comparative methods with secondary data in the form of annual financial reports obtained from the Indonesia Stock Exchange (BEI). The sample in this research is the balance sheet and profit and loss report of PT Indo Tambangraya Mega Tbk for the 2018-2022 period. Based on the results of research using fundamental methods consisting of Return On Assets (ROA), Return On Equity (ROE), Deb To Equity Ratio (DER), and Earning Per Share (EPS), the results show that in particular ROA, ROE, DER and EPS has a positive and significant influence in determining share prices. When viewed simultaneously ROA, ROE, DER and EPS have a positive and significant influence on stock prices